Mechanical damage of fresh produce in postharvest transportation: Current status and future prospects. (June 2022) - Al-Dairi, Mai; Pathare, Pankaj B.; Al-Yahyai, Rashid; Opara, Umezuruike Linus
Abstract: Background: Incidence of postharvest losses in the fresh produce value chain is a worldwide concern facing food security and sustainability. Postharvest losses can occur along the supply chain stages such as harvesting, storing, handling, packaging, transporting, and marketing. Mechanical damage caused by vibration is one of the most common quality challenges to fresh produce during transit. Scope and approach: Mechanical damage of fresh produce can cause considerable economic losses by reducing quality and can result in severe food safety concerns. Understanding the factors affecting fresh produce damage during transportation is significant in developing strategies for reducing postharvest losses. We review transport as an essential component in the postharvest supply chain and critically discuss the adverse effect on fresh produce, mainly due to vibration. Key findings and conclusions: The experimental approaches applied to measure the vibration levels during transport of fresh produce are presented. Factors influencing the vibration level discussed herein include surface condition, vehicle speed, vibration duration, vibration direction, packaging unit, etc. A comprehensive discussion on the effects of packing unit type and surface of packaging material, location of the package on the vehicle, and height of the package in a stack on the vibration level is presented. Vibration during transportation is difficult to avoid; however, applying good management practices like improving the refrigeration system, utilization of appropriate packaging, and incorporating suitable cushioning materials can reduce produce damage during transit. Overall, careful selection of better solutions to this critical issue can help to reduce fresh produce susceptibility to vibration damage during road transport and thereby reduce incidence of postharvest losses of fresh commodities. Highlights: Vibration during transit can affect the fresh produce quality. Factors affecting for vibration level during transit are reviewed. Role of packaging on vibration level is discussed. Use of simulation studies are reviewed. Strategies to fresh produce damage reduction during transit are discussed.